2006
DOI: 10.4319/lo.2006.51.2.0936
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton photoacclimation and photoadaptation in response to environmental gradients in a shelf sea

Abstract: Variability in the photosynthetic performance of natural phytoplankton communities, due to both taxonomic composition and the physiological acclimation of these taxa to environmental conditions, was assessed at contrasting sites within a temperate shelf sea region. Physiological parameters relating to the structure of the photosystem II (PSII) antenna and processes downstream from PSII were evaluated using a combination of fast repetition rate fluorescence, oxygen flash yields, spectral fluorescence, and 14 C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
212
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 197 publications
(237 citation statements)
references
References 41 publications
22
212
3
Order By: Relevance
“…Differences in photoacclimation strategy are due to the heterogeneity in photosynthetic structure and accessory pigment composition between species, influencing the rate and quantity of photons received by the photosystem (Wilhelm, 1990). Some species acclimate by changing the size of the light harvesting antenna of the individual reaction centre, while others increase the total number of reaction centres, keeping antenna size constant (Falkowski and LaRoche, 1991;Moore et al, 2006). As with temperate diatoms (Ruban et al, 2004;Dimier et al, 2007;Lavaud et al, 2007), SO-and sea ice diatoms are highly plastic to fluctuations in light with a strong dependence on rapid and reversible xanthophyll cycling (Moisan et al, 1998;Moisan and Mitchell, 1999;Kropuenske et al, 2009;Petrou et al, 2011a,c), however, not all species utilise the same strategies, nor have the same level of physiological plasticity (Kropuenske et al, 2009;Mills et al, 2010;Petrou et al, 2011a).…”
Section: Lightmentioning
confidence: 99%
“…Differences in photoacclimation strategy are due to the heterogeneity in photosynthetic structure and accessory pigment composition between species, influencing the rate and quantity of photons received by the photosystem (Wilhelm, 1990). Some species acclimate by changing the size of the light harvesting antenna of the individual reaction centre, while others increase the total number of reaction centres, keeping antenna size constant (Falkowski and LaRoche, 1991;Moore et al, 2006). As with temperate diatoms (Ruban et al, 2004;Dimier et al, 2007;Lavaud et al, 2007), SO-and sea ice diatoms are highly plastic to fluctuations in light with a strong dependence on rapid and reversible xanthophyll cycling (Moisan et al, 1998;Moisan and Mitchell, 1999;Kropuenske et al, 2009;Petrou et al, 2011a,c), however, not all species utilise the same strategies, nor have the same level of physiological plasticity (Kropuenske et al, 2009;Mills et al, 2010;Petrou et al, 2011a).…”
Section: Lightmentioning
confidence: 99%
“…Dark-adapted measurements of the effective absorption cross section, s PSII , are affected by both physiological (phenotypic) and taxonomic (genotypic) signatures of the phytoplankton community (Suggett et al, 2004;Moore et al 2005Moore et al , 2006. Specifically, smaller s PSII values are indicative of large eukaryotes or cyanobacteria but may also indicate a down-regulation in light harvesting for photochemistry; higher s PSII values are indicative of smaller eukaryotes but also an up-regulation of light harvesting for photochemistry (Suggett et al, 2004).…”
Section: Variability Of Psii Light Absorptionmentioning
confidence: 99%
“…However, these approximations of non-photochemical quenching assume that the dark-adapted effective absorption cross-section remains constant throughout the water column. Recent evidence from both the laboratory (Suggett et al, 2004) and field (Moore et al, 2005(Moore et al, , 2006) has demonstrated that s PSII,478 can be highly variable both between taxa and with photoacclimatory state. This would imply that the dark-adapted effective absorption cross-section is not constant with depth where distinct phytoplankton populations occur at different depths within the water column, as frequently occurs within tropical and subtropical Atlantic provinces (Zubkov et al, 2000;Barlow et al, 2002).…”
Section: Frr Fluorescence and Fluorescence Quenchingmentioning
confidence: 99%
See 2 more Smart Citations